Pengaruh Perceived Organizational Support Dan Organizational Citizenship Behavior Terhadap Task Performance (Studi Kasus Pada Divisi HRD PT. ASTRA DAIHATSU SUNTER) - Sulastriningsih, Dewi (Jurnal Ecodemica: Jurnal Ekonomi, Manajemen, dan Bisnis, 2014)
ABSTRACTPerceived Organizational Support (Kaufman and Stamper) can be defined as beliefs of workerâs seriousness level of organization in participate a boost to them related to the development of the potential and capacity to achieve higher performance. Perceptions of organizational support as the employeesâ beliefs that organization regard and reward their contributions to the success of the organization. Organizational Citizenship Behavior often defined as the individuals behaviour who have the freedom to choose indirectly or explicitly which approved by the reward system, and contribute to the effective and effisience functions of organization (Organ et al,). According to Borman and Motowidlo et. Al. Task performance is the activitiy that directly involve the core tasks fulfillment or support the achievement of the tasks involved organization "technical core". This research conducted at the Division of HRD PT. Astra Daihatsu Sunter. The number of samples are 50 people. By using path analysis, the results show that there were positive and significant effect simultaneously between perceived organizational support and organizational citizenship behavior toward task performance for about 26.8 %, while partially perceived organizational support toward task performance has positive and significant effect for about 44.10 % and organizational citizenship behavior toward task performance has positive effect but not significant for about 16.10 % .Keywords: Perceived Organizational Support, Organizational Citizenship Behavior, Task Performnce